As condutas pró-ambientais no Brasil: uma abordagem sistemática das atividades de aventura no incitar do sujeito ecológico - Andrade, Rafael Ferreira de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
In a time that the technological development and the living conditions in the urban environment (work, housing, etc.) seem to distance people from nature, at the same time that economic development follows destroying the environment on a global scale, it is consistent that a growing number of people are looking to break these barriers spending more time with pleasant and exciting moments in nature (MARINHO, 2008). Considering this, and taking into account that Brazil presents a growing plant mass loss and, consequently, a falling in biodiversity, any strategies that could catalyze efforts, as Adventure Activities in Nature are very important for environmental education. Promoting this and other strategies within this context, it may be possible to provide a more conscious and meaningful contact with the natural environment, based on encouraging new habits and values .This study aims to analyze, in the available researches from Portal CAPES, the approaches of adventure activities as a tool to raise sensitization and environmental awareness, evidencing how this issue is being addressed in academic realm. This qualitative study is developed through the union of documentary and exploratory researches, taking into account as bibliographic database the researches published at national journals from the Portal of the Higher Education Personnel Improvement Coordination (CAPES). Data were analyzed through Thematic Content Analysis Technique. Inclusion criteria were adopted only articles in full, in Portuguese, published between 2010 and 2015. In all, were analyzed 18 articles which go ahead with the scope of the search. The sample of published articles, added to the literature review, supported the inference that the adventure activities have a key role in the consolidation of pro-environmental attitudes. However, in this research, it was noticed that very few studies in Brazil dedicated to the understanding of the adventure activities as a major...

Devido à excessiva perda de massa vegetal nos diferentes biomas do Brasil, e, por conseguinte, o crescente número de espécies em extinção, perda de solo, assoreamento de rios, etc., se fazem necessárias medidas que convoquem as pessoas a estreitar o vínculo ser humano-natureza, bem como, a estimular a preservação do patrimônio natural. Uma das possibilidades nesse sentido está centrada na vivência de atividades de aventura. Sendo assim, o presente estudo teve como objetivo analisar, nas pesquisas disponibilizadas no portal de periódicos da Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), as abordagens sobre atividades de aventura como ferramenta à sensibilização e conscientização ambiental, evidenciando de que forma essa questão está sendo tratada no âmbito acadêmico. O presente estudo, de natureza qualitativa, foi desenvolvido por meio da união de pesquisa documental e pesquisa exploratória. Como critério de inclusão foram adotados apenas artigos na íntegra, em português, publicados entre 2010 e 2015. Os dados foram analisados descritivamente, por meio da Técnica de Análise de Conteúdo Temático. Ao todo, foram submetidos à análise 18 artigos que se coadunavam com o escopo da pesquisa. As atividades de aventura na natureza demonstraram ser um importante instrumento para a educação ambiental, principalmente pela capacidade de incitar mudanças atitudinais que, por ventura, representarão novas posturas e condutas frente ao meio ambiente, consolidando o desencadeamento do comportamento pró-ambiental. No entanto, com esta pesquisa, percebeu-se que pouquíssimos estudos no Brasil dedicaram-se à compreender as atividades de aventura como fenômeno principal no despertar dessa consciência ambiental
Keywords: Educação ambiental; Ecologia humana; Natureza - Influência do homem; Proteção ambiental; Sustentabilidade; Ecoturismo; Atividades físicas de aventura; Lazer; Periódicos eletrônicos - 2010-2015; Brasil